Analisis Kemampuan Menulis Teks Persuasif melalui Media Poster Lingkungan pada Siswa Madrasah Ibtidaiyah - Daniar Khumairotul Anwariyah; Kholik Kholik (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research aims to conduct an in-depth analysis of fourth-grade students' persuasive writing skills through environmental posters at MI Ihyaussalafiyah. The primary focus is to investigate how students transform direct field observations into systematic and coherent text structures. This encompasses the ability to identify environmental issues, construct logical arguments, and employ effective persuasive vocabulary to influence readers. The study employs a qualitative case study method involving 16 fourth-grade students as subjects. Data were collected using the